Les calebasses nka’a kügha : du contexte d’origine à la mise en exposition en Europe - Ninon Arbez-Gindre (Les Cahiers de l'École du Louvre)
The jawbones of enemies killed by the Bamum were hung from these calabashes. These symbols of victory were the used for rituals and considered the dynasty’s regalia. During the colonial period, they became artefacts collected by Europeans, particularly missionaries. Their acquisition led to a break with their original context and a change in function, and the calabashes were reused for propaganda purposes, particularly to justify the missionaries’ actions in the field and demonstrate their effectiveness. This article examines a set of four Nka’a kügha calabashes from the Bamum Kingdom (Cameroon), collected by the Société des Missions évangéliques de Paris (SMEP) in the 1920s and 1930s and now in the British Museum, and the museums of ethnography in Neuchâtel and Geneva. Their circulation, reuse in different social universes, reconnection with the context of origin and restitution have placed the calabashes at the centre of contemporary museum issues, starting with the exhibition of works made using human remains.